The learning curve and its contribution to the human talent performance in organizations: a theoretical review - Cardona-Arbeláez, Diego Alonso; Del Río-Cortina, Jorge Luis; Romero-Severiche, Ana Karina; Lora-Guzmán, Harold (Universidad Pedagógica y Tecnológica de Colombia, 2019)
The aim of this article is to carry out a theoretical review of the learning curve, its origins, models and main applications. A documentary investigation was carried out, for which specialized databases were consulted, addressing the main authors and the characteristic aspects of each model. The findings indicate the importance of studying learning curves, both at the individual, group and organizational levels. The latter can be a source for decision-making in companies, since the different learning curve models can provide information referring to: production goals, performance evaluation, labor estimation, and price and cost optimization, to create competitive advantages. The reviewed works highlight the benefit of learning curves in topics such as: planning, training and process control. It is concluded that the learning curves, although they began in the aviation industry, have been disseminated to various industrial sectors, with the contribution of new mathematical models for their estimation.